Extraction from Adjunct Islands in Swedish - Müller, Christiane (Norsk Lingvistisk Tidsskrift, 2017)
This paper investigates restrictions on the reported possibility to extract from adjunct clauses in Swedish. I report results from an acceptability judgement study showing that extraction is constrained by the following factors: (i) the degree of syntactic integration of the adjunct clause, (ii) the internal syntax of the adjunct clause, and (iii) semantic coherence. Regarding factor (i), extraction is degraded when it occurs out of peripheral adverbial clauses, which are not sufficiently integrated with their host clause. Factor (ii) constrains extraction from clauses that have a relatively complex internal structure and possess an illocutionary potential. Factor (iii) refers to the observation that extraction is enhanced if the matrix and adjunct clause event are related by a contingent relation such as causation or enablement. From a cross-linguistic perspective, Swedish (and presumably also Danish and Norwegian) still stand out in allowing extraction from at least a subset of finite adjunct clauses. This is considered to be impossible in other languages.